Precipitation reaction in alpha-Cu-Al-Ag alloys - Silva, R.A.G.; Adorno, A.T. [UNESP]; Carvalho, T.M. [UNESP]; Magdalena, A.G. [UNESP]; Santos, C.M.A. [UNESP] (Rede Latino-Americana de Materiais, 2011)
The Ag-rich precipitates formation reaction in the Cu-9.22%at. Al-4.66%at. Ag, Cu-9.31%at. Al-5.83%at. Ag and Cu-9.37%at. Al-7.08%at. Ag alloys was studied using microhardness change measurements with temperature and time, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and X-ray diffractometry (XRD). The results indicated that the Ag-rich phase formation is an interface controlled process with a zero-order mechanism, due to the amount of unsolved Ag that makes the precipitation reaction rate independent of Ag concentration.
Keywords: Ag additions; Cu-based alloys; kinetics